Study guide [for] business statistics for management and economics - Daniel, Wayne W., 1929- (Houghton Mifflin, 1995)
Introduction to business statistics. Organizing and summarizing data. Some elementary probability concepts. Some important probability distributions. Some important sampling distributions. Statistical inference I, II. Analysis of variance...